Responses to song playback vary with the vocal performance of both signal senders and receivers - Moseley, Dana L.; Lahti, David C.; Podos, Jeffrey (Proceedings of the Royal Society. B, Biological sciences, 2013)
Mating signals of many animal species are difficult to produce and thus should indicate signaler quality. Growing evidence suggests that receivers modulate their behaviour in response to signals with varying performance levels, although little is known about if and how responses are affected by receiver attributes. To explore this topic we conducted two experiments with swamp sparrows, Melospiza georgiana, in which we challenged territorial males with playback of songs with trill rates that were natural, digitally reduced, or digitally elevated (control-, low- and high-performance stimuli, respectively). In our first experiment, we found that males responded more aggressively to control songs than to low-performance stimuli, that low-performance stimuli with the most severe trill-rate reductions elicited the weakest aggressive responses, and that the subjects' own trill rates predicted aggressive responses. In our second experiment, we found that male responses to high-performance stimuli varied significantly, in ways predicted by two factors: the degree to which we had elevated stimulus performance levels of high-performance stimuli, and subjects' own vocal performance levels. Specifically, males were less aggressive towards stimuli for which we had elevated performance levels to higher degrees, and subject males with higher vocal performances themselves responded more aggressively. These findings together offer a novel illustration of how responses to aggressive signals may rely not just on signal attributes, but also on attributes of responding animals themselves.